2004
DOI: 10.1385/bter:101:1:01
|View full text |Cite
|
Sign up to set email alerts
|

Trace Element Status (Se, Cu, Zn) in Healthy Portuguese Subjects of Lisbon Population: A Reference Study

Abstract: Serum levels of selenium, copper, and zinc were systematically determined in healthy subjects of the Lisbon population. The sample consisted of 183 blood donors of both genders who were divided into two age groups: 20-44 and 45-70 yr of age; relationships with gender, age, the lipid profile, and tobacco consumption were investigated. In the female group, the intake of oral contraceptives and pregnancy were considered for the youngest women, and hormonal replacement therapy (HRT) was taken into account for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
2
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(41 citation statements)
references
References 54 publications
4
30
2
4
Order By: Relevance
“…In this study, risk subjects presented higher levels of selenium in plasma than the reference ones, which might be related to the presence of approximately 80% of hyperlipidemic subjects in the risk group (70). This association could in part be the result of the binding of selenium to lipoproteins, mainly LDLs, which are recognized as having significant amounts of selenium (71).…”
Section: Redox Balance In Atherosclerosis 69mentioning
confidence: 59%
“…In this study, risk subjects presented higher levels of selenium in plasma than the reference ones, which might be related to the presence of approximately 80% of hyperlipidemic subjects in the risk group (70). This association could in part be the result of the binding of selenium to lipoproteins, mainly LDLs, which are recognized as having significant amounts of selenium (71).…”
Section: Redox Balance In Atherosclerosis 69mentioning
confidence: 59%
“…In serum, it has been documented for Cu by Ghayour-Mobarhan et al (2005) and Kouremenou-Dona et al (2006); for Se by Lopes et al (2004). In brain, Markesbery et al (1984), Ongkana et al (2010) and Tohno et al (2010)  data converted from nmol/L Table 6.…”
Section: Agementioning
confidence: 99%
“…For changes of Se, Cu and Zn in serum, see Lopes et al (2004) and Ghayour-Mobarhan et al (2005). For Zn variations in brain, see Ongkana et al (2010).…”
Section: Gendermentioning
confidence: 99%
“…Trace element levels have been estimated by some investigators to establish reference values for the healthy population group and factors that may affect serum levels of trace elements [7]. Ghayour-Mobarhan et al [8] reported that serum copper, zinc, and selenium concentrations are influenced by physiological conditions such as age, diet, and gender [8,9].…”
Section: Introductionmentioning
confidence: 99%